1996
DOI: 10.1023/a:1016903508976
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Invasive blood pressure measurement is used in patients with unstable haemodynamics. The demand of the accuracy of these measurements is high. The reliability of the reproduced signal strongly depends on the measurement system's dynamic characteristic-its resonance frequency and damping factor. These characteristics were examined with the frequency response method, which is valuable for second and higher order systems. Most of the pressure measuring systems in use in clinical practice have low damping factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A planecta port is useful to avoid babbling and/or bacterial contamination [ 10 ], but it decreases the natural frequency of the kit. ROSE™ is useful to optimise the frequency characteristics of the kits with no or one planecta port [ 11 , 12 ]. However, the kit with two planecta ports showed underdamping, and when ROSE™ was inserted, it showed overdamping due to the very low natural frequency.…”
Section: Discussionmentioning
confidence: 99%
“…A planecta port is useful to avoid babbling and/or bacterial contamination [ 10 ], but it decreases the natural frequency of the kit. ROSE™ is useful to optimise the frequency characteristics of the kits with no or one planecta port [ 11 , 12 ]. However, the kit with two planecta ports showed underdamping, and when ROSE™ was inserted, it showed overdamping due to the very low natural frequency.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we demonstrated that the nanocomposite hydrogels containing Mg 2+ effectively enhanced the osteogenic differentiation of hMSCs and contributed to in situ bone regeneration . By further investigating the functions of Mg 2+ in cellular metabolism, we noticed that it is also a critical cofactor for the enzymatic activity of alkaline phosphatase (ALP) . ALP catalyzes the hydrolysis of monoesters of phosphoric acid to generate inorganic phosphate, which is essential for bone mineralization .…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of multiple FTPs in the circuit causes a marked reduction in the natural frequency, resulting in underdamping of kit circuits and undershooting of the arterial intra-arterial pressure waveform [3]. In contrast, the insertion of the ROSE TM system considerably increases the damping coefficient of the circuits and subsequently decreases underdamping [7,8]. However, overdamping was still observed when two FTPs and the ROSE TM system were combined [3].…”
Section: Discussionmentioning
confidence: 99%